Tribological Dry Sliding Behavior of Chopped Carbon Fiber Reinforced Polyetheretherketone - Chumaevskii A. V.; Ivanov A. N. Aleksey Nikolaevich; Filippov A. V. Andrey Vladimirovich; Rubtsov V. E. Valery Evgenjevich; Kolubaev Е. А. Evgeny Aleksandrovich (2017, 2017)
Title screen